2023
DOI: 10.3390/analytics2040042
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Clustering Algorithms for Customer Segmentation in the UK Retail Market

Jeen Mary John,
Olamilekan Shobayo,
Bayode Ogunleye

Abstract: Recently, peoples’ awareness of online purchases has significantly risen. This has given rise to online retail platforms and the need for a better understanding of customer purchasing behaviour. Retail companies are pressed with the need to deal with a high volume of customer purchases, which requires sophisticated approaches to perform more accurate and efficient customer segmentation. Customer segmentation is a marketing analytical tool that aids customer-centric service and thus enhances profitability. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…Using VOSviewer, we performed co-occurrence analysis, which was achieved using clustering. Clustering is the grouping of objects according to their similar attributes [65]. The authors [66] developed VOSviewer in 2010 [67] and demonstrated the use of VOSviewer to perform co-occurrence analysis of research publications using clustering.…”
Section: Co-occurrencementioning
confidence: 99%
“…Using VOSviewer, we performed co-occurrence analysis, which was achieved using clustering. Clustering is the grouping of objects according to their similar attributes [65]. The authors [66] developed VOSviewer in 2010 [67] and demonstrated the use of VOSviewer to perform co-occurrence analysis of research publications using clustering.…”
Section: Co-occurrencementioning
confidence: 99%